ATYPICAL PRESENTATION OF SEVERE PROGNATHISM IN PATIENT WITH CONGENITAL ADRENAL HYPERPLASIA - Arsaythamby , Kumarendren; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders due to mutation in the genes that regulate adrenal steroidogenesis. The commonest form is due to 21-OH enzyme deficiency in which the classic form is divided into salt-losing or simple virilizing types. CASE A 20-year-old Malay male has been under our follow-up since his early infancy. He was diagnosed to have a salt-losing form of CAH in the neonatal period as he had adrenal crises associated with skin hyperpigmentation. The boy was treated with oral hydrocortisone 10–15 mg/m²/day and oral fludrocortisone 150 mcg to 200 mcg per day. However, starting from the age of five, he experienced medication adherence issues due to inadequate supervision and logistical challenges. At the age of 15 years, he was diagnosed to have testicular adrenal rest tumour. He later complained of progressive difficulty chewing his food due to the development of mandibular hyperplasia or prognathism. He was treated with high dose glucocorticoid and ketoconazole to control his hyperandrogenism and referred to the maxillofacial team for further management. CONCLUSION Despite being detected early and managed promptly, the outcome of treatment relies strongly on the compliance of the patient. Non-adherence to medication may lead to unforeseen detrimental complications which could worsen the long-term prognosis.